PENEGAKAN HUKUM TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR BERDASARKAN PASAL 362 KUHP DI WILAYAH KEPOLISIAN RESOR KAMPAR - Affan, Kharul; Saputra, Rian Prayudi; Firmanto, Fakhry (Pahlawan Tuanku Tambusai University, 2022)
Law enforcement is an attempt to express the moral image contained in the law. The rise of motor vehicle theft that is growing, strategic locations and the ease of committing the crime of motor vehicle theft, and the difficulty of finding evidence of perpetrators by investigators make the crime of motor vehicle theft increasingly attractive to criminals. The formulation of the problem in this study is how to enforce the law on the crime of motor vehicle theft and what are the obstacles and how to enforce the law on the crime of motor vehicle theft. The research used is empirical research. The results of the study found that law enforcement on the crime of motor vehicle theft was carried out by following up on reports from victims of theft through the SPKT which then made a BAP which then carried out an investigation and when it was complete the investigator handed over the suspect to the police and if it was not known or found, further investigation was carried out and a DPO letter was made . Internal constraints faced include inadequate facilities and infrastructure, disconnected information networks, inadequate police officers, and lack of budget support. Preventive efforts are urging the public to be more careful, giving advice not to park vehicles carelessly and giving double keys. His repressive efforts carried out further investigations to uncover other perpetrators of motor vehicle theft. Keywords: Crime, Theft, Motor Vehicles